CD47 is an adverse prognostic factor and a therapeutic target in gastric cancer. (16th June 2015) - Yoshida, Kazumichi; Tsujimoto, Hironori; Matsumura, Kouji; Kinoshita, Manabu; Takahata, Risa; Matsumoto, Yusuke; Hiraki, Shuichi; Ono, Satoshi; Seki, Shuhji; Yamamoto, Junji; Hase, Kazuo
Abstract CD47 is an antiphagocytic molecule that acts via ligation to signal regulatory protein alpha on phagocytes; its enhanced expression and therapeutic targeting have recently been reported for several malignancies. However, CD47 expression in gastric cancer is not well documented. Immunohistochemical expression of CD47 in surgical specimens was investigated. Expression of CD47 and CD44, a known gastric cancer stem cell marker, were investigated in gastric cancer cell lines by flow cytometry. MKN45 and MKN74 gastric cancer cells were sorted by fluorescence‐activated cell sorting according to CD44 and CD47 expression levels, and their in vitro proliferation, spheroid‐forming capacity, and in vivo tumorigenicity were studied. In vitro phagocytosis of cancer cells by human macrophages in the presence of a CD47 blocking monoclonal antibody (B6H12) and the survival of immunodeficient mice intraperitoneally engrafted with MKN45 cells and B6H12 were compared to experiments using control antibodies. Immunohistochemistry of the clinical specimens indicated that CD47 was positive in 57 out of 115 cases, and its positivity was an independent adverse prognostic factor. Approximately 90% of the MKN45 and MKN74 cells expressed CD47 and CD44. CD47hi gastric cancer cells showed significantly higher proliferation and spheroid colony formation than CD47lo, and CD44hiCD47hi cells showed the highest proliferation in vitro and tumorigenicity in vivo. B6H12 significantly enhanced in vitro phagocytosis of cancer cells by human macrophages and prolonged the survival of intraperitoneal cancer dissemination in mice compared to control antibodies. In conclusion, CD47 is an adverse prognostic factor and promising therapeutic target in gastric cancer.